Novel methods for the analysis of toxicants in bronchoalveolar lavage fluid samples from e‐cigarette, or vaping, product use‐associated lung injury cases: Selected petroleum distillates. (2nd September 2020) - De Jesús, Víctor R.; Chambers, David M.; Reese, Christopher; Braselton, Martha; Espinosa, Paul; Corstvet, Joseph; Blount, Benjamin C.
Abstract : Rationale: Over 2700 e‐cigarette, or vaping, product use‐associated lung injury (EVALI) cases were reported to the Centers for Disease Control and Prevention (CDC) during August 2019–February 2020. Bronchoalveolar lavage (BAL) fluid samples from 51 EVALI and 99 non‐EVALI cases were analyzed for toxicants including petroleum distillates. We describe a novel method to measure petroleum distillates in BAL fluid using gas chromatography–mass spectrometry (GC/MS). Methods: n ‐Hexane, n ‐heptane, n ‐octane, methylcyclopentane, and cyclohexane were measured in BAL fluid specimens by headspace solid‐phase microextraction/GC/MS. We created and characterized BAL fluid pools from non‐EVALI individuals to determine assay accuracy, precision, linearity, limits of detection (LODs), and analytical specificity. All measurements were conducted in accordance with the rigorous method validation procedures of CDC's Division of Laboratory Sciences. Results: Matrix validation experiments showed that calibration curves in BAL fluid and saline had similar slopes, with differences less than 5%. Assay precision ranged from 1.98% to 18%. In addition, the LODs for the five analytes ranged from 0.05 to 0.10 μg/L, and their linearity was confirmed with R 2 values >0.99. The analysis of selected petroleum distillates in BAL fluid analysis was shown to be comparable with their analysis in blood in which the 95th percentiles are below detection. Conclusions: We developed and validated a method to quantify petroleum distillates in BAL fluid specimens using GC/MS. The assay provided precise and accurate analyses of EVALI and non‐EVALI BAL fluid specimens in support of CDC's EVALI response. This method is applicable to the determination of a broad range of volatile organic compounds in BAL fluid specimens.